Wilms' Tumor Protein 1 and Enzymatic Oxidation of 5-Methylcytosine in Brain Tumors: Potential Perspectives - Ramsawhook, Ashley; Ruzov, Alexey; Coyle, Beth (Frontiers in Cell and Developmental Biology, 2018)
The patterns of 5-methylcytosine (5mC) and its oxidised derivatives, 5-hydroxymethylcytosine, 5-formylcytosine and 5-carboxylcytosine (5caC) are reportedly altered in a range of cancers. Likewise, Wilms’ Tumour protein 1 (WT1), a transcription factor essential for urogenital, epicardium and kidney development exhibits aberrant expression in multiple tumours. Interestingly, WT1 directly interacts with TET proteins that catalyse the enzymatic oxidation of 5mC and exhibits high affinity for 5caC-containing DNA substrates in vitro. Here we review recent developments in the fields of Tet-dependent 5mC oxidation and WT1 biology and explore potential perspectives for studying the interplay between TETs and WT1 in brain tumours.